Traditional Supplementary Food Based on Local Wisdom of Tangerang for Early Childhood - Fitria Budi Utami; Maya Lestari; Fahmy Ulfah Mawaddah; Romdoni Romdoni; Triani Triani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Traditional food not only represents cultural richness, but also has an important value in building healthy eating habits and understanding of halal principles, especially in early childhood. This study aims to explore the introduction of halal traditional food through the supplementary feeding program (SFP) in Early Childhood Education (ECE) institutions in Tangerang Regency. The qualitative descriptive method was used in this study, involving five ECE institutions as research subjects. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman analysis model. The results showed that each ECE institution had a diverse supplementary feeding program, with a carefully selected halal traditional food menu. Children showed high enthusiasm for the food served, while parents gave full support to this program. Challenges faced include limited resources and knowledge about traditional food. However, there are opportunities to improve this program through collaboration with local communities and increased training for teachers. This study concludes that the introduction of halal traditional food to early childhood can be effective with the right support, providing a positive impact on understanding culture and religious values from an early age. This study also provides recommendations for increasing food variety and a deeper understanding of culinary and halal aspects.